Temperature-dependent local structure and lattice dynamics of 1T-TiSe2 and 1T-VSe2 probed by X-ray absorption spectroscopy - Pudza, Inga; Polyakov, Boris; Pudzs, Kaspars; Welter, Edmund; Kuzmin, Alexei (Elsevier B.V., 2024)
The local atomic structure and lattice dynamics of two isostructural layered transition metal dichalcogenides (TMDs), 1T-TiSe2 and 1T-VSe2, were studied using temperature-dependent X-ray absorption spectroscopy at the Ti, V, and Se K-edges. Analysis of the extended X-ray absorption fine structure (EXAFS) spectra, employing reverse Monte Carlo (RMC) simulations, enabled tracking of the temperature evolution of the local environment in the range of 10–300 K. The atomic coordinates derived from the final atomic configurations obtained using the RMC method were used to calculate the partial radial distribution functions (RDFs) and the mean-square relative displacement (MSRD) factors for the first ten coordination shells around the absorbing atoms. Characteristic Einstein frequencies and effective force constants were determined for Ti[sbnd]Se, Ti[sbnd]Ti, V[sbnd]Se, V[sbnd]V, and Se[sbnd]Se atom pairs from the temperature dependencies of MSRDs. The obtained results reveal differences in the temperature evolution of lattice dynamics and the strengths of intralayer and interlayer interactions in TiSe2 and VSe2. © 2024 Elsevier B.V. --//-- This is an open-access article Inga Pudza, Boris Polyakov, Kaspars Pudzs, Edmund Welter, Alexei Kuzmin, Temperature-dependent local structure and lattice dynamics of 1T-TiSe2 and 1T-VSe2 probed by X-ray absorption spectroscopy, Physica B: Condensed Matter, Volume 685, 2024, 415995, ISSN 0921-4526, https://doi.org/10.1016/j.physb.2024.415995 published under the CC BY-NC-ND 4.0 licence.
B.P. and A.K. thank the support of the Latvian Council of Science, Latvia project No. LZP-2020/1-0261. The experiment at the PETRA III synchrotron was performed within proposal No. I-20210625 EC. The synchrotron experiment has been supported by the project CALIPSOplus under the Grant Agreement 730872 from the EU Framework Programme for Research and Innovation HORIZON 2020. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Effective force constants; Extended X-ray absorption fine structure; Interlayer and intralayer coupling; Reverse Monte Carlo simulations; Transition metal dichalcogenides